International organizations and higher education policy [ thinking globally, acting locally? - Bassett, Roberta Malee; Maldonado, Alma (International studies in higher education, 2009)
nalyzes the impact influential organizations such as the World Bank, UNESCO, OECD, WTO, and bilateral aid agencies have at different levels of higher education policy development and implementation